Building a conceptual framework in image reinvention: A case study of SWISS, Switzerland’s national airline - PANG, A. (Institutional Knowledge at Singapore Management University, 2012)
If image repair is the strategy to use during crises, what can organizations do after the crisis isover? Organizations cannot possibly be contented with only coping with the fallout, butultimately desire public affection and even more success than pre-crisis. To this end, reinventiontakes place when management takes decisive actions to engage in innovation and risk-taking, andinvolve communication. Image reinvention is posited as a strategy an organization could considerafter it undergoes a bruising crisis that questions its raison d’etre (Pang, 2011). The organizationsheds its previous image and rebuilds a new image by reconstituting what it stands for to itsstakeholders. Theoretical concept will be built from identity, brand and image literature andintegrated with Liu’s (2010) System Network of Failure Framing. The concept is applied on alongitudinal case study of how SWISS, Switzerland’s national airline, reinvented its image fromsuccessor Swissair in 2001 to become “Best Western European airline” in 2011 (SWISS, 2011a).